2023
DOI: 10.7759/cureus.48727
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Stress and Immune Response in Surgery: A Psychoneuroimmunological Perspective

Taufiqa Reza,
Han Grezenko,
Chad Barker
et al.

Abstract: Psychoneuroimmunology (PNI) offers a deep dive into the nexus between emotional stress, immunity, and surgical outcomes. In this narrative review, we first trace PNI’s historical roots, providing a foundational understanding of its evolution. We then dissect its significance across the surgical journey, from the preoperative phase through to postoperative recovery. It becomes evident through our exploration that emotional stress has profound implications for surgery, notably influencing wound healin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The discussion on psychoneuroimmunology (PNI) is crucial in unraveling the complexities of the nocebo effect. PNI, which delves into the interplay among psychological, neurological, and immunological factors, plays a pivotal role in understanding how behavior and immunity reciprocally influence each other ( Reza et al, 2023 ). This field challenges the conventional view of the immune system as an autonomous entity and offers a comprehensive bio-psycho-social perspective on health and illness.…”
Section: Discussionmentioning
confidence: 99%
“…The discussion on psychoneuroimmunology (PNI) is crucial in unraveling the complexities of the nocebo effect. PNI, which delves into the interplay among psychological, neurological, and immunological factors, plays a pivotal role in understanding how behavior and immunity reciprocally influence each other ( Reza et al, 2023 ). This field challenges the conventional view of the immune system as an autonomous entity and offers a comprehensive bio-psycho-social perspective on health and illness.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Research has demonstrated that both psychological and physiological stress exert substantial impacts on immune system, subsequently influencing the processes involved in wound healing. 9 , 10 Chronic stress has the potential to induce immunosuppression, which can hinder the body's innate healing processes. This is especially pertinent for patients with liver cirrhosis, as their condition frequently imposes substantial physical and psychological strains.…”
Section: Introductionmentioning
confidence: 99%